Contextualizing Developmental Math Content into Introduction to Sociology in Community Colleges. - Parker, Stuart; Traver, Amy; Cornick, Jonathan (TRAILS: Teaching Resources and Innovations Library for Sociology, 2018)
Across community colleges in the United States, most students place into a developmental math course that they never pass. This can leave them without the math skills necessary to make informed decisions in major areas of social life and the college credential required for participation in growing sectors of our economy. One strategy for improving community college students’ pass rate in developmental math courses is the contextualization of developmental math content into the fabric of other courses. This article reviews an effort to contextualize developmental math content (i.e., elementary algebra) into Introduction to Sociology at Kingsborough Community College and Queensborough Community College, both of the City University of New York, during the spring 2016 semester. Data from a pretest/posttest control-group design implemented across the two campuses reveals the significance of this strategy for some sociology students’ grasp of discrete mathematical skills and success in developmental math.